Higher Education in Russia: The Rise of Economic Dominance - S. S. Studnikov (Мир новой экономики)
Choosing a university is not an easy matter, and, as a rule, it is a task of multi-criteria optimization, and one of the weighty criteria is career prospects. At present, the children of those who themselves were applicants during the USSR collapse started to choose a university. At that time, it was believed that only elite universities (Moscow State University, MGIMO, etc.) would serve as a social lift to the most prestigious organizations of business, government, and science. In part, this can explain the almost total desire of modern school graduates to have a higher education, although often it is the desire of their parents. Using the example of the higher education market in Russia, the author examines the tendencies of universities’ concentration, their stratifiation into three levels with different institutional conditions and the dominance of the upper levels (alpha universities) over the lower ones (beta and gamma universities). The article analyses Russian alpha universities’ features against the background of a similar global hierarchy and identifies development trends for universities after the explosive introduction of distance learning technologies.